PENGARUH CITRA MEREK, KEPERCAYAAN MEREK DAN PERSEPSI HARGA TERHADAP MINAT BELI ULANG KONSUMEN - Dian Afiati, 09.05.51.0012; Basiya, R. (Students Journal of Economic and Management, 2013)
In a high competitive business, a company should maintain their customers. Therefore, its a need to search some variables influence which are increasing their repurchase intention as a method to maintain the customers. Researcher used purposive accidental sampling, this research find the 100 sample size respondents. The analytical data result shows that some research methods has good correlation and all the research hypothesis can beproved. The conclusion is brand image, brand trust and positive price perception and significant effect on consumer repurchase intentions. According to the research results get can be taken the theoretical implication that this research gives justification to the former research in which brand image, brand trust and price perception have influen to the consumer repurchase intention.Key words: Brand Image, Brand Trust, Price Perception, Repurchase Intention Consumer